2014
DOI: 10.1155/2014/213106
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Probabilistic Routing Algorithm for Internet of Things

Abstract: In the future network with Internet of Things (IoT), each of the things communicates with the others and acquires information by itself. In distributed networks for IoT, the energy efficiency of the nodes is a key factor in the network performance. In this paper, we propose energy-efficient probabilistic routing (EEPR) algorithm, which controls the transmission of the routing request packets stochastically in order to increase the network lifetime and decrease the packet loss under the flooding algorithm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…The data history of the neighboring node is checked by forwarding node . And if the data is already available with the previous node than data packet forwarding is avoided by the forwarding node to reduce redundancy [14]. In IoT, records transmission from home to target is a main fear in changing environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data history of the neighboring node is checked by forwarding node . And if the data is already available with the previous node than data packet forwarding is avoided by the forwarding node to reduce redundancy [14]. In IoT, records transmission from home to target is a main fear in changing environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In that, they estimated the Pocket Delivery Ratio using the existing data traffic. Sang et al [15] suggested EEPR (Energy Efficient probabilistic routing for IoT) algorithm using residual energy of each node and ETX metric in the context of AODV protocol. The proposed algorithm controlled the request packet forwarding process in order to reduce the packet loss and network congestion.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It builds a Destination Oriented Directed Acyclic Graph (DODAG). Many metrics may be used to construct a DODAG: the Expected Number of Transmissions (ETX) [29], the remaining energy of the devices… Energy-Efficient Probabilistic Routing (EEPR) [30] is an alternative solution for routing in an IoT environment. It is based on the same idea of AODV but the transmission of a RREQ packet follows a certain forwarding probability that depends on the residual energy and the ETX metric The proposed mathematical equation shows that the forwarding probability will be high if the ETX metric is low and the residual energy is high.…”
Section: Iot Routing Protocolsmentioning
confidence: 99%